Spatial disparities and development policy - Kochendörfer-Lucius, Gudrun; Pleskovic, Boris (Berlin Workshop series, 2009)
The Berlin Workshop Series 2009 presents selected papers from meetings held from September 30 - October 2, 2007, at the 10th Annual Forum co-hosted by InWEnt and the World Bank in preparation for the Bank's World Development Report. At the 2007 meetings, key researchers and policy makers from Europe, the United States, and developing countries met to identify and brainstorm on agriculture the development challenges and successes that are later examined in-depth in the World Development Report 2009. This volume presents papers from the Berlin Workshop sessions on issues relating to Understanding.